Edukasi Tentang Manfaat Inisiasi Menyusui Dini (IMD) Pada Ibu Postpartum di Klinik H. Syahrudin - Tambunan, Lili Yulian; Umamy, Farida; Ratnasari, Fika; Wulandari, Hardini (Jurnal Masyarakat Indonesia (Jumas), 2023)
This community service is entitled "Education about the benefits of early initiation of breastfeeding (IMD) In Postpartum Mothers at the H. Syahrudin Clinic". This community service aims to determine the level of knowledge of postpartum mothers about the effect of early initiation of breastfeeding on uterine involution. The method used in this community service is by providing education and counseling directly to postpartum mothers regarding the effect of early initiation of breastfeeding (IMD) on uterine involution. The results of community service show a significant increase in knowledge about the effect of early initiation of breastfeeding (IMD) on uterine involution after implementing this method. The conclusion of this community service activity is that direct education and counseling regarding the application of early initiation of breastfeeding can make the uterine involution process run smoothly, and can be an alternative to prevent bleeding because the uterus contracts well, and health workers really help postpartum mothers in implementing early initiation of breastfeeding (IMD).